AN ANALYSIS OF CODE MIXING USED BY CINTA LAURA “TANGGAPAN CINTA LAURA KALO DI TAWARIN MASUK PARTAI POLITIK” AT METRO TV YOUTUBE CHANNEL - Islamia, Hikmatul; Wafa, Hosnol; Sutrisno, Adi; Andayani, Sri (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
This study found the phenomenon of code mixing in Cinta Laura's conversational interactions on one of the TV stations uploaded on the Metro TV YouTube channel. The phenomenon of code mixing not only occurs in direct interactions but also often occurs in communication on social media. This happens because the dynamics of language continue to change in the social and technological context. Communication is common on social media such as Instagram, WhatsApp, TikTok, and YouTube. YouTube is a means of communicating with many people, and this has a significant impact on its users, both positive and negative. This study aims to describe the forms of code mixing types in Cinta Laura's conversation. This study uses Hoffman's code-mixing theory as the main basis for analyzing the collected data. The research design uses a descriptive qualitative method, with data collection techniques through observation and recording. The data source is all of Cinta Laura's conversations that contain code-mixing. The data was analyzed from one video with a duration of 42 minutes and 34 seconds, which was found in 97 code-mixing events. The analysis results show that 80 data were found that included intra-sentence code-mixing 7 data included intra-lexical code-mixing and 6 data included Involving Change of Pronunciation. This study also found a combination of two types of code mixing, mixing between intra-sentence and intra-lexical, in 4 data. This finding shows that the dynamics of language use in social media and digital communication are very complex and influenced by various social and technological factors. The results of this study are expected to provide a deeper understanding of how code mixing occurs in everyday communication.